Characterization and biological properties of peptides isolated from dried fermented cow milk products by RP‐HPLC: Amino acid composition, antioxidant, antihypertensive, and antidiabetic properties. Issue 7 (19th June 2021) - Alu'datt, Muhammad H.; Al‐u'datt, Doa'a G. F.; Alhamad, Mohammad N.; Tranchant, Carole C.; Rababah, Taha; Gammoh, Sana; Althnaibat, Rami M.; Daradkeh, Mohammad G.; Kubow, Stan
Abstract : Abstract: This study aimed to assess the biological properties of peptide fractions isolated from dried fermented dairy products (jameed) as influenced by processing. Peptide fractions were separated by reversed‐phase high‐performance liquid chromatography (RP‐HPLC) from salted (Sa) and unsalted (Us) cow milk jameed after drying the fermented curd by sun drying (Sd) or freeze‐drying (Fd) and were characterized for their antioxidant capacity and inhibitory activity toward angiotensin I‐converting enzyme (ACE) and α‐amylase. Sd samples showed more numerous peptide peaks in RP‐HPLC chromatograms than Fd samples, regardless of the salt content. High antioxidant activity was evidenced in several peptide fractions from FdUs jameed (including fractions 1, 2, 4, 7, 8, 9, and 10), SdUs jameed (1, 2, 5, 7, and 9), and FdSa jameed (2, 5, 6, and 9). By contrast, peptide fractions from SdSa (1, 2, 3, 5, 8, and 9), SdUs (4, 5, and 10), and FdUs (5, 6, and 8) jameed displayed the highest ACE inhibitory activity. Similarly, the highest inhibition of α‐amylase was obtained with fractions from SdSa (1, 2, 3, 4, 5, 6, 8, and 9), SdUs (2 and 6), and FdUs (1, 7 and 9) jameed. A significant negative correlation was evidenced between antioxidant activity and anti‐α‐amylase activity of peptide fractions from SdSa jameed. These findings demonstrate that cow milk jameed is a source of bioactive peptides with antioxidant, anti‐ACE, and anti‐α‐amylase properties in vitro, which can be tailored by adjusting the salt content and the drying conditions. Practical Application: This study shows that cow milk jameed, a staple fermented food in several Mediterranean countries, can serve as a useful source of multifunctional bioactive peptides with potential antioxidant, hypotensive, and hypoglycemic effects, which may help prevent and manage chronic health conditions such as hypertension, type 2 diabetes, and the metabolic syndrome. The bioactivities of certain peptide fractions were enhanced by lowering the salt content of jameed or by the drying method. The relatively simple RP‐HPLC method described in this study can be used to isolate the peptide fractions of interest for further characterization and use as functional ingredients.